Phenotypic Screening of H1-Antihistamines Identifies Promethazine and Rupatadine as Active Compounds Against Toxocara canis Infective Larvae - Taís C. Silva; Julia Godoy-Silva; Monique C. Amaro; João V. Silva-Silva; Thiago H. Doring; Leonardo L. G. Ferreira; Adriano D. Andricopulo; Josué de Moraes (Pharmaceuticals)
Background: Parasitic worm infections remain among the most prevalent and neglected health issues worldwide, affecting both humans and animals. Toxocariasis, caused by Toxocara spp., is a widespread zoonosis with significant public health and economic implications. Current anthelmintic treatments show limited efficacy, particularly against tissue-migrating larvae, underscoring the urgent need for new therapeutic options. This study aimed to evaluate the anthelmintic potential of H1 antihistamines as repurposed drug candidates against Toxocara canis. Methods: Twenty-two H1 antihistamines were screened for larvicidal activity against infective third-stage (L3) larvae of T. canis. Larval motility and morphology were assessed, and compounds with the highest efficacy were further investigated using density functional theory (DFT) to explore their electronic properties. Molecular docking simulations were also performed to predict interactions with T. canis β-tubulin. Results: Promethazine and rupatadine exhibited significant larvicidal effects, surpassing albendazole in reducing larval motility and inducing a distinct contorted morphology not observed in control or albendazole-treated larvae. DFT analyses suggested a strong electron-acceptor capacity, indicating a potential redox-based mechanism of action. Docking studies revealed favorable binding to the colchicine site of T. canis β-tubulin. Conclusions: This is the first report of larvicidal activity of antihistamines against T. canis, supporting their potential as repurposed therapeutic agents for the treatment of zoonotic helminthiases, particularly those caused by tissue-migrating nematodes.